The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1210/jc.2011-3432
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 Receptor Signaling Is Required for Weight Loss after Gastric Bypass Surgery

Abstract: MC4R is the first gene identified that is required for the sustained effects of bariatric surgery. The need for MC4R signaling for the weight loss effects of RYGB in mice underscores the physiological mechanisms of action of this procedure and demonstrates that RYGB both influences and is dependent on the normal pathways that regulate energy balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 37 publications
10
102
1
5
Order By: Relevance
“…Given the role of the central MC4R system in the control of energy balance (5) and pathophysiology of human obesity (119), (120). These studies suggest either that non-MC4R-mediated mechanisms by which RYGBP affects energy balance are not powerful enough to overcome complete absence of MC4R signaling or that the MC4R system is intrinsic to the biological response to RYGBP ( Figure 2).…”
Section: Role Of the Mc4r Pathwaymentioning
confidence: 99%
“…Given the role of the central MC4R system in the control of energy balance (5) and pathophysiology of human obesity (119), (120). These studies suggest either that non-MC4R-mediated mechanisms by which RYGBP affects energy balance are not powerful enough to overcome complete absence of MC4R signaling or that the MC4R system is intrinsic to the biological response to RYGBP ( Figure 2).…”
Section: Role Of the Mc4r Pathwaymentioning
confidence: 99%
“…Most of the recent animal studies and some studies in humans have examined the role of the melanocortin system, which seems to be central to many peripheral and brain-derived stimuli that control eating and body weight (55,92,93,157). In humans, the sufficiency of one functional MC4r gene for effective RYGB outcome was indicated in some studies, including RYGB or VSG-operated humans (157).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
“…With the exception of a few rare variants, 35 all studies looking at patients with MC4R variants found that gastric bypass surgery was fully effective. 14,33,35,36 However, gastric banding in one rare patient with complete loss of MC4R functionality did not produce a lasting reduction in body weight.…”
Section: Potential Underlying Mechanisms For Change In Set Pointmentioning
confidence: 89%
“…14 Another study concluded that complete absence of MC4R signaling in homozygous, but not in heterozygous knockout mice, abrogated the effectiveness of RYGB. 33 Interpretation of that study is made difficult due to high mortality, low number of animals and the unusually low weight gain in MC4R-deficient mice, which was less than observed in other studies using homozygous MC4R-deficient mice. 34 Using chronic pharmacological blockade of brain MC4R signaling 3-4 months after RYGB or sham surgery in rats (see Discussion above and Figure 1), we concluded that brain MC4R signaling is not the critical mechanism by which RYGB lowers defended body weight level.…”
Section: Potential Underlying Mechanisms For Change In Set Pointmentioning
confidence: 91%